Every nonprofit's tax guide : how to keep your tax-exempt status & avoid IRS problems - Fishman, Stephen (Berkeley, California : Nolo, 2016)
Nonprofits enjoy privileges not available to other organizations. But these privileges come at a price: Nonprofits must comply with special IRS rules and regulations. This book covers what your organization must do to maintain its tax-exempt status. Whether you are just starting your nonprofit or are well established, you'll find all the information you need to avoid the most common issues nonprofits run into with the IRS.
Nonprofits and the IRS -- Annual IRS filings--the form 990 -- Record keeping and accounting -- Volunteers, employees, and independent contractors -- Charitable giving--the basics and cash donations -- Property donations -- Excessive compensation, sweetheart deals, and other ways to get in trouble with the IRS -- Nonprofits that make money and UBIT -- Lobbying and political campaign activities -- Help beyond this book.
Includes bibliographical references and index.
Keywords: Nonprofit organizations -- Taxation -- United States -- Popular works; Charitable uses, trusts, and foundations -- Taxation -- United States -- Popular works